Rancang Bangun Kontrol Temperatur dan Cahaya Ruangan Menggunakan Raspberry PI - Hary Firdian; Ardianto Wibowo; Rika Perdana Sari (Politeknik Caltex Riau, 2018)
The human body will always try to maintain a normal state with a perfect body system so that it can adjust to changes that occur outside the body. But the ability to adjust itself to the outside temperature is if the change in outside body temperature does not exceed 20% for heat conditions and 35% for cold conditions from the normal state of the body (Tjitro, 2004). The temperature that is considered normal for Indonesians is between 240 C to 260 C. Because heat is easier to affect body temperature, humans often look for cooler places. To overcome this problem an application is needed to facilitate controlling the temperature in the room. In this project the application with the help of Raspberry Pi and sensors to keep the room temperature stable.